Pengaruh Struktur Modal Dan Profitabilitas Terhadap Nilai Perusahaan Pada PT United Tractors Tbk Periode 2014-2023 - Salbila Octanadanti; Arif Hidayat (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the effect of capital structure and profitability on firm value in PT United Tractors Tbk for the period 2014–2023. The variables used in this research include capital structure measured by the Debt to Equity Ratio (DER), profitability measured by the Return on Assets (ROA), and firm value measured by the Price to Book Value (PBV). This research employs a quantitative approach with multiple linear regression analysis. The results indicate that partially, capital structure (DER) has no significant effect on firm value, with a significance value of 0.100 > 0.05. Meanwhile, profitability (ROA) has a significant and negative effect on firm value, with a significance value of 0.003 < 0.05 and a regression coefficient of –0,069. Simultaneously, capital structure and profitability significantly influence firm value, as evidenced by the F-statistic of 9.836 greater than the F-table value of 4.74 with a significance level of 0.009 < 0.05. These findings suggest that the combination of financing decisions and profitability performance jointly shapes investor perceptions of firm value, although DER individually does not play a significant role.